PERBERDAYAAN MASYARAKAT MISKIN MELALUI KELOMPOK USAHA BERSAMA DI KELURAHAN BALLA KECAMATAN BARAKA KABUPATEN ENREKANG (Fakultas Dakwah dan Komunikasi, 2021)
This study aims to determine the implementation of joint business groups in empowering the poor in Balla Village, Baraka District, Enrekang Regency, and supporting and inhibiting factors in Balla Village, Baraka District, Enrekang Regency. This research is qualitative research using a sociological approach. The results of this study indicate that the implementation of joint business groups, namely the formation of joint business groups, application of joint business groups, sources of funding, assistance in empowering joint business groups. Then the supporting factors are mentoring with integrity and professionalism, support from the Social Service, and the inhibiting factor, namely the lack of human resources. The poor who participate in the joint business group program must be truly confident and must be enthusiastic in trying to do anything. Do not because there are problems that arise, make the problem an excuse for not wanting to try to make ends meet. It is hoped that the Social Service will pay more attention to human resources so that they can make people more creative in an effort to improve the economy in each family, especially in Balla Village, Baraka District, Enrekang Regency.